Modeling the effects of climate change on the irrigation water requirements of wheat and canola in the TR21 Thrace Region using CROPWAT 8.0 - Deveci, Huzur; Önler, Buse; Erdem, Tolga (Frontiers in Sustainable Food Systems, 2025)
Accurately predicting future changes in plant water requirements is crucial for effective irrigation scheduling. This study modeled the effect of climate change on irrigation water requirements for wheat and canola in the TR21 Thrace Region using CROPWAT 8.0. The HadGEM2-ES and MPI-ESM-MR models were used to simulate reference (1971–2000) and future short-term (2031–2040) and long-term (2051–2060) periods under RCP4.5 and RCP8.5 scenarios. The effects of climate change on reference evapotranspiration (ETo), crop evapotranspiration (ETc), and irrigation water requirements (IWR) for wheat and canola cultivation were modeled. As a result, compared to the reference period, ETo values increased by 4.5%–%17.1 (2.396–2.906 mm day−1) and 5.8%–%17.7 (2.110–2.533 mm day−1), while ETc values increased by 5.7%–%17.0 (438–595 mm season−1) and 6.3%–%17.0 (374–464 mm season−1) for wheat and canola, respectively. IWR values varied between −2.4 and 35.8% (158.8–321.3 mm season−1) for wheat and − 2.5 and 48.8% (106.5–238.6 mm season−1) for canola. When the results obtained from wheat and canola are compared, it is predicted that ETo will be 11–14% higher, ETc will be 14–23% higher, and IWR will be 19–43% higher for wheat than for canola. In addition, an analysis of the relationship between temperature and ETo, ETc, and IWR showed the pattern ETo > ETc > IWR, suggesting that while temperature strongly influences ETo and ETc, it is not the sole determinant of IWR. These findings provide valuable projections for farmers, agriculturalists, local administrators, planners, and decision-makers to support adaptation strategies for climate variability.